Efficacy and safety of a non-immersive virtual reality-based neuropsychological intervention for cognitive stimulation and relaxation in patients with critical illness: study protocol of a randomized clinical trial (RGS-ICU) - Marta Godoy-González; Josefina López-Aguilar; Sol Fernández-Gonzalo; Gemma Gomà; Lluís Blanch; Santiago Brandi; Sergi Ramírez; Joel Blasi; Paul Verschure; Gemma Rialp; Miquel Roca; Margalida Gili; et al. (BMC Psychiatry)
Abstract Background Experiencing a critical illness may be a stressful life event that is also associated with cognitive dysfunction during and after the intensive care unit (ICU) stay. A deep-tech solution based on non-immersive virtual reality, gamification and motion capture called Rehabilitation Gaming System for Intensive Care Units (RGS-ICU) has been developed that includes both cognitive stimulation and relaxation protocols specifically designed for patients with critical illness. This study aims to evaluate whether the cognitive and relaxation protocols of the RGS-ICU platform are 1) effective in improving neuropsychological outcomes during and after ICU stay and 2) safe for patients with critical illness. Methods This is a study protocol for a multicenter longitudinal randomized clinical trial. At least 80 patients with critical illness will be included: 40 experimental subjects and 40 control subjects. Patients in the experimental group will receive daily 20-min sessions of cognitive stimulation and relaxation with the RGS-ICU platform adjuvant to standard ICU care in their own rooms during the ICU stay and until discharge from the ICU or up to a maximum of 28 days after randomization, provided they are alert and calm. Patients in the experimental group will be constantly monitored as part of standard ICU care to ensure the safety of the intervention and that no avoidable adverse events occur. Patients in the control group will receive standard ICU care. The primary outcome is objective cognition 12 months after ICU discharge, assessed with a composite index including measures of attention, working memory, learning/memory, executive function and processing speed. The secondary outcome is the safety of the intervention, assessed by considering the number of sessions terminated early due to unsafe events in physiological parameters. Other outcomes are comfort experienced during the ICU stay, and subjective cognition, mental health (anxiety, depression and post-traumatic stress disorder), functionality and health-related quality of life 12 months after ICU discharge. Discussion The expected results are 1) better neuropsychological outcomes during and after the ICU stay in patients in the experimental group compared to patients in the control group and 2) that the cognitive and relaxation protocols of the RGS-ICU platform are safe for patients with critical illness. Trial registration Clinicaltrials.gov NCT06267911. Registered on February 20, 2024.